2022
DOI: 10.1001/jamainternmed.2021.6445
|View full text |Cite
|
Sign up to set email alerts
|

Payer-Specific Negotiated Prices for Prescription Drugs at Top-Performing US Hospitals

Abstract: NIH) during the conduct of the study. Mr Crusan reported receiving grants from the NIH during the conduct of the study. Dr Heit reported receiving grants from the NHLBI, NIH during the conduct of the study. No other disclosures were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 3 publications
(4 reference statements)
1
13
0
Order By: Relevance
“…Negotiated prices in our study varied greatly within hospitals as well as across hospitals, which is consistent with many previous reports on price transparency 17‐19 . Price variations have largely been attributable to differences in market power between insurers and providers.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Negotiated prices in our study varied greatly within hospitals as well as across hospitals, which is consistent with many previous reports on price transparency 17‐19 . Price variations have largely been attributable to differences in market power between insurers and providers.…”
Section: Discussionsupporting
confidence: 89%
“…Negotiated prices in our study varied greatly within hospitals as well as across hospitals, which is consistent with many previous reports on price transparency. [17][18][19] Price variations have largely been attributable to differences in market power between insurers and providers. Our subanalysis demonstrated that hospital-level factors, particularly 340B status and geographic location in the northeast and west, also appear to significantly impact price markups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent analysis of 10 high-expenditure drugs at 20 top-rated hospitals found that 45% were noncompliant with requirements to disclose payer-specific negotiated drug prices that, when disclosed, were typically much higher than Medicare payment limits . Our study builds on this work by additionally estimating hospital markup relative to acquisition costs and the magnitude of price variation over the course of treatment in a larger and more clinically homogeneous cohort of NCI-designated cancer centers.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the findings may underestimate the extent of price markups and variations if centers chose not to disclose any drug prices or selected drug prices to prevent public concern about price-gouging . Fourth, we were unable to ascertain the proportion of patients at each hospital covered by specific insurance plans; thus, the findings may not accurately reflect average prices weighted by payer and plan mix . Fifth, we were unable to estimate the extent to which negotiated prices were associated with patient out-of-pocket costs, which depend on plan benefit design; for example, higher prices would not directly translate to higher costs for patients who have already reached out-of-pocket spending caps.…”
Section: Discussionmentioning
confidence: 99%